PERKEMBANGAN KESENIAN TUTUNGGULAN KAMPUNG SAMBAWA KABUPATEN TASIKMALAYA - Wulandari, Wulandari; Cahyana, Agus; Falah, Asep Miftahul (ATRAT: Jurnal Seni Rupa, 2021)
The development of Tutunggulan art in Sambawa District Tasikmalaya is the title of this research, the purpose of which is to describe the general picture of the birth of traditional art Tutunggulan also the development of Tutunggulan art in Sambawa village. To dig up the data used qualitative research methods, and ethnography. Data collected through observation techniques, interviews and documentation. All data is processed with reduction, display and verification techniques. The findings and results of research on the development of Tutunggulan art that is about the origin, implementation, development, function, characteristics, meaning, cultural value, and efforts of the art Tutunggulan Sambawa village. This art is hereditary from generation to generation not only serves as a means of communication and entertainment but also as an expression of the ideology of Sambawa village people. Traditional art of Tutunggulan in Sambawa which is known to be ritual and sacred began to shift and little by little lost its function. Slowly, it began to grow less developed and abandoned by the supporting community. This condition can be said as a stage of the decline of the development of Tutunggulan art in Sambawa. Keywords: Tutunggulan Art, Sambawa Village, Traditional Art------------------------------------------------------------------------------------------Perkembangan kesenian Tutunggulan di kampung Sambawa Kabupaten Tasikmalaya merupakan judul dari penulisan makalah ini, tujuannya untuk mendeskripsikan mengenai gambaran umum lahirnya kesenian tradisional Tutunggulan juga perkembangan kesenian Tutunggulan dikampung Sambawa. Penulisan ini mengguna pendekatan antropologi budaya, yaitu proses pengumpulan data dan mencatat bahan-bahan guna mengetahui keadaan masyarakat (kelompok etnik) yang bersangkutan dalam keadaan sekarang tanpa melupakan masa lampau. Pembahasan makalah perkembangan kesenian Tutunggulan yaitu mengenai sejarah, ciri khas, makna, fungsi, dan nilai budaya local, serta persepsi dan pengaruh masyarakat, perkembangan juga upaya masyarakat dalam mempertahankan kesenian tradisional Tutunggulan di kampung Sambawa. Kesenian ini turun-temurun dari generasi ke generasi tidak hanya berfungsi sebagai alat komunikasi dan hiburan tetapi sekaligus juga untuk mengekspresikan wujud ideologi masyarakat kampung Sambawa. Kesenian tradisional Tutunggulan dikampung Sambawa yang dikenal bersifat ritual dan sakral mulai tergeser dan sedikit demi sedikit kehilangan fungsinya. Perlahan demi perlahan mulai kurang berkembang dan ditinggalkan oleh masyarakat pendukungnya. Kondisi ini dapat dikatakan sebagai tahap dari penurunan perkembangan kesenian Tutunggulan di kampung Sambawa. Kata kunci: Kesenian Tutunggulan, Kampung Sambawa, Kesenian Tradisional